Respuesta :

Answer:

r=5

Step-by-step explanation:

Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :  

                    -3*(4*r-8)-(-36)=0  

Step by step solution :

Step  1  :

Step  2  :

Pulling out like terms :

2.1     Pull out like factors :

  4r - 8  =   4 • (r - 2)  

Equation at the end of step  2  :

 (0 -  12 • (r - 2)) -  -36  = 0  

Step  3  :

Step  4  :

Pulling out like terms :

4.1     Pull out like factors :

  60 - 12r  =   -12 • (r - 5)  

Equation at the end of step  4  :

 -12 • (r - 5)  = 0  

Step  5  :

Equations which are never true :

5.1      Solve :    -12   =  0

This equation has no solution.

A a non-zero constant never equals zero.

Solving a Single Variable Equation :

5.2      Solve  :    r-5 = 0  

Add  5  to both sides of the equation :  

                     r = 5  

One solution was found :

                  r = 5


brainliest pllzz thx god bless

Answer:

r=5

Step-by-step explanation:

-3(4r - 8)=-36

The first step is to distribute the -3

-3*4r -3*-8 = -36

-12r +24 = -36

Subtract 24 from each side.

-12r + 24-24 = -36-24

-12r = -60

Divide each side by -12

-12r/-12 = -60/-12

r=5